2023
DOI: 10.3389/fpsyt.2023.1211889
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effects of attention problems on the link between parenting style and internet gaming disorder in adolescents

Abstract: BackgroundPositive and negative parenting styles as well as psychiatric comorbidities including attention deficit hyperactivity disorder (ADHD) have been associated with internet gaming disorder (IGD) in children and adolescents. We hypothesized that ADHD and parenting style would be associated with IGD in adolescents. In addition, psychological status could mediate the link between parenting style and the severity of IGD.MethodsA total of 256 adolescents with IGD and 211 healthy internet game players and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…One study obtained results revealed that low-quality parenting behaviors in which parents experience more conflicts and partner's sabotage in parenting practices are associated with more authoritarian and negative parenting styles. 34 Negative parenting styles, such as rejection and overprotection, tend to be predictors of smartphone addiction and online gaming disorder in children and adolescents, 35,36 whereas positive parenting styles are protective, for example, children with warm and democratic parenting styles are less likely to become addicted to smartphones. 37,38 Therefore, it is reasonable to hypothesize that prolonged technological interference in parent-child interactions not only diminishes parenting quality but also impacts parenting styles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study obtained results revealed that low-quality parenting behaviors in which parents experience more conflicts and partner's sabotage in parenting practices are associated with more authoritarian and negative parenting styles. 34 Negative parenting styles, such as rejection and overprotection, tend to be predictors of smartphone addiction and online gaming disorder in children and adolescents, 35,36 whereas positive parenting styles are protective, for example, children with warm and democratic parenting styles are less likely to become addicted to smartphones. 37,38 Therefore, it is reasonable to hypothesize that prolonged technological interference in parent-child interactions not only diminishes parenting quality but also impacts parenting styles.…”
Section: Literature Reviewmentioning
confidence: 99%